2018
DOI: 10.1186/s12905-018-0650-9
|View full text |Cite
|
Sign up to set email alerts
|

Men’s awareness of cervical cancer: a qualitative study

Abstract: BackgroundsAs HPV is a sexually transmitted virus, men are crucial in the prevention of cervical cancer, but research about men’s awareness on cervical cancer is limited. Therefore, in this study, we investigated men’s awareness toward women’s cervical cancer, to thoroughly understand the viewpoints of men, and to emphasize the centrality of the role of men in the prevention of cervical cancer.MethodsA qualitative descriptive design was chosen to explore men’s awareness of women’s cervical cancer. Twelve men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
6
18
1
Order By: Relevance
“…The importance of social networks in influencing health-related knowledge and behaviors have been previously described (22,23,24).. Studies have also documented ways in which social networks can be important sources of support for promoting health and wellbeing (25,26,27).. Similar to other studies that have explored male involvement in cervical cancer prevention, we found that most male respondents had poor knowledge of HPV as a risk factor in cervical cancer (28,29,30).. Consequently, there is an urgent need to implement educational interventions aimed at increasing men's knowledge of risk factors and empowering them to be more proactive in preventing cervical cancer. Furthermore, the cultural norms of masculinity that dictate roles and set expectations that discourage male involvement in promoting women's reproductive health or their ability to engage in cervical cancer prevention should be addressed.…”
Section: Discussionsupporting
confidence: 79%
“…The importance of social networks in influencing health-related knowledge and behaviors have been previously described (22,23,24).. Studies have also documented ways in which social networks can be important sources of support for promoting health and wellbeing (25,26,27).. Similar to other studies that have explored male involvement in cervical cancer prevention, we found that most male respondents had poor knowledge of HPV as a risk factor in cervical cancer (28,29,30).. Consequently, there is an urgent need to implement educational interventions aimed at increasing men's knowledge of risk factors and empowering them to be more proactive in preventing cervical cancer. Furthermore, the cultural norms of masculinity that dictate roles and set expectations that discourage male involvement in promoting women's reproductive health or their ability to engage in cervical cancer prevention should be addressed.…”
Section: Discussionsupporting
confidence: 79%
“…Individually and collectively, members of social networks provide social, emotional and financial support for those dealing with a health issue. In this study, we found that characteristics of social Similar to other studies that have explored male involvement in cervical-cancer prevention, we found that most male respondents had poor knowledge of HPV as a risk factor in cervical-cancer (28,29,30). Consequently, there is an urgent need to implement educational interventions aimed at increasing men's knowledge of risk factors and empowering them to be more proactive in preventing cervical-cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, previous studies have found that fewer men knew someone who had cervical cancer, with 10% of survey respondents in a community-based study from rural and urban sites in Swaziland [33], 5% of respondents in a study conducted at HIV clinics in rural and urban areas of Kenya [35], and no respondents among urban men in Ghana reporting a direct contact [37]. We also found higher knowledge of cervical cancer risk factors and of screening services than has been previously reported --although some important gaps in knowledge remain [27,28,30,35,38]. For example, men in our study, compared to a 2014 study among mostly HIV-positive men in Nyonga…”
Section: Discussionmentioning
confidence: 56%